A ZIF-67-derived lamellar CoP@C cocatalyst for promoting photocatalytic hydrogen evolution from water. (5th February 2023) - Wang, Junwen; Song, Tao; Su, Lei; Xu, Haoyang; Bai, Xiaoyu; Zhou, Lina; Tu, Weixia
Abstract: Photocatalytic hydrogen evolution from water is one of the top issues to achieve green hydrogen energy and utilize solar energy. Construction of cocatalyst is a major part for efficient photocatalysts. Lamellar flower-like CoP@C cocatalyst is synthesized via the phosphating of cobalt precursor derived from metal-organic framework ZIF-67. Different from usual phosphating of ZIF-67 directly, a typical solvothermal treatment of ZIF-67 contributes to tuning the formation of C nanodots on the lamellar CoP. CoP@C as cocatalyst exhibits a remarkable role of improving photocatalytic activity for hydrogen evolution. CoP@C/CdS composite shows a photocatalytic hydrogen evolution rate of 164.4 mmol g −1  h −1, which is much higher than those of pure CdS and other CoP/CdS photocatalysts. The heterojunction and interaction are verified between CoP@C and CdS. Light absorption and photoelectric properties of CoP@C/CdS are enhanced accompanying with strong reduction ability. A type-Ⅱ transfer path of photoelectrons is underway in CoP@C/CdS photocatalyst, accelerating the separation of electron-hole pairs and the transfer of carriers, and further resulting in the promoted photocatalytic performance. This work provides a suitable way to achieve carbon nanodots involved metal compound cocatalysts for efficient hydrogen production. Graphical abstract: Image 1 Highlights: A lamellar flower-like CoP@C cocatalyst is constructed from ZIF-67-derived Co(OH)2 precursor. A typical solvothermal treatment of ZIF-67 contributes to tuning the formation of C nanodots on CoP. The present CoP@C/CdS exhibits much higher photocatalytic activity for H2 evolution than other CoP/CdS. The CoP@C/CdS heterostructure brings strong reduction ability and superior light adsorption.